Investment appraisal of a plantation establishment for intensive apple production - Apáti, F.; Felföldi, J. (International Journal of Horticultural Science, 2006)
For fruits, establishing intensive apple-orchards requires the highest amount of investment cost, while the returns depend on many factors. Based on farm and bibliography data we appraised an investment in a model in some variations that are the most used in practice (100% owner's capital and 55% owner's capital +45%o subsidies). The profitability of the investment has been analysed using the methods of NPV (Net Present Value) and DPP (Dynamic Payback Period). The essence of our analysis is a sensitivity analysis with the optimistic, pessimistic and realistic combinations of the yield and the market price. Plantation establishment financed by only own (corporate's) sources turns into profitable over 7-10 years in average and favourable cases, but the opposite is the case in unfavourable circumstances. By subsidy of 45% for investments, it is highly possible to return by the fifth or sixth year after the year of establishment, but it can return by the twelfth year even in unfavourable case.